Arbuscular Mycorrhizal Fungal Community Composition in Carludovica palmata, Costus scaber and Euterpe precatoria from Weathered Oil Ponds in the Ecuadorian Amazon - Garcés-Ruiz, Mónica; Senés-Guerrero, Carolina; Declerck, Stéphane; Cranenbrouck, Sylvie (Frontiers in Microbiology, 2017)
Arbuscular mycorrhizal fungi (AMF) are ubiquitous to most natural and anthropized ecosystems, and are often found in polluted environments. However, their occurrence and community composition in highly weathered petroleum polluted-soils has been infrequently reported. In the present study, two ponds of weathered crude oil and their surrounding soil from the Charapa field in the Amazon region of Ecuador were selected and root colonization by AMF of their native plants investigated. The AMF community was further analyzed in three selected plant species (i.e. Carludovica palmata, Costus scaber and Euterpe precatoria) present in the two ponds and the surrounding soil. A fragment covering partial SSU, the whole ITS and partial LSU rDNA region was amplified (i.e.1.5 kb), cloned and sequenced from the roots of each host species. AMF root colonization exceeded 56% in all plant species examined and no significant difference was observed between sites or plants. For AMF community analysis, a total of 138 AMF sequences were obtained and sorted into 32 OTUs based on clustering (threshold ≥ 97%) by OPTSIL. The found OTUs belonged to the genera Rhizophagus (22%), Glomus (31%), Acaulospora (25%) and Archaeospora (22%). Glomus and Archaeospora were always present regardless of the plant species or the site. Acaulospora was found in the three plant species and in the two ponds while Rhizophagus was revealed only in the surrounding soil in one plant species (Euterpe precatoria). Our study contributed to the molecular community composition of AMF and revealed an unexpected high presence of four AMF genera which have established a symbiosis with roots of native plants from the amazon forest under high polluted soil conditions.